Managing 21st century libraries - Pugh Lyndon (Maryland Scarecrow Press, 2005)
Managing 21st Century Libraries is primarily concerned with creating the circumstances in which people can maximize the use of their talents and generating the opportunities for people to work with others in ways that engage all of the abilities of every
Keywords: Library administration; Library personnel management